Seroprevalence of IgM and IgG antibodies to toxoplasma infection in human immunodeficiency virus-positive antiretroviral therapy-naive individuals - Saloni Garg; Babita Sharma; Rameshwari Bithu; Nitya Vyas (Wolters Kluwer Medknow Publications, 2019)
Introduction: Toxoplasmosis, a zoonotic disease infecting about one-third of the world's population, is caused by intracellular parasite Toxoplasma gondii. It is a major health concern in immunocompromised individuals as in human immunodeficiency virus (HIV)-positive patients. The aim of the study was to determine the seroprevalence of T. gondii infection among HIV-infected antiretroviral therapy-naive individuals attending Integrated Counseling and Testing Center. Materials and Methods: It was a cross-sectional observational study conducted at a tertiary care hospital between April 2015 and March 2016 on 400 HIV-positive patients and 100 HIV-negative healthy adults. Anti-toxoplasma IgM and IgG antibodies were detected using a commercially available enzyme-linked immunosorbent assay kit. Sociodemographic and associated risk factors for T. gondii infection were obtained and the data were analyzed using SPSS version 17.0. Results: Seroprevalence of anti-toxoplasma antibodies among 400 HIV-positive patients and 100 HIV-negative healthy adults was 19.75% and 11%, respectively. Majority of seropositive individuals were in the childbearing age groups. Out of 79 toxoplasma-seropositive cases, 10 were clinically confirmed cases of toxoplasma encephalitis (TE). The mean CD4+ T-lymphocyte count of HIV-positive patients was 255.32 ± 221.19 cells/cmm. Conclusion: The seroprevalence of toxoplasma infection is significantly higher in HIV-positive patients than in HIV-negative healthy individuals. It is important to test all HIV-positive patients for toxoplasma antibodies to prevent life-threatening complication and TE in these patients.